NÆRBILLEDER AF DET EKSOTISKE: Etnografiske illustrationer af Påskeøen fra anden halvdel af 1700-tallet - Brander, Elsa Cristina de Lima Agra Amorim (Tidsskriftet Antropologi, 2004)
This article discusses the theoretical and pragmatic dialogue between the instructions given to the artists who participated in European scientific expeditions and the production of ethnographic illustrations. The discrepancy between methodological criteria and the empirical portrayal of exotic Others indicates an important dilemma: that the European representations of alien cultures were deeply rooted in European aesthetic idiosyncrasies and ideals of primitiveness. The French artist Gaspard Duché de Vancy (ca. 1750-1788) who travelled on François Galaup de Lapérouse’s scientific expedition (1785-1788) portrayed the society of Easter Island not according to what he actually observed, but rather to the captain’s distrustful judgement of the natives of Easter Island. In an effort to solidify a rather biased portrayal of the natives, the artist incorporated specific ethnographic devices, including exotic attire, weaponry and the gigantic monoliths, endeavouring to give his illustrations a more ethnographic and thus realistic outlook. Furthermore, this article discusses an illustration of Easter Island that the German traveller Johann Reinhold Forster (1729-1798) made, and which he included in his own German translation of Lapérouse’s travels. A study of Forster’s illustration indicates that the author generously borrowed crucial elements from Duché de Vancy’s original painting, and from two other paintings, made by the British painter William Hodges. By uncovering how expedition artists incorporated aesthetic idiosyncrasies into their compositions, this article uncovers how ethnographic illustrations were manipulated according to an exotic decor, where the alien reality was at first patch-worked and as a result constructed.